1992
DOI: 10.1002/jrs.1250230802
|View full text |Cite
|
Sign up to set email alerts
|

SERS study of the conformational transition of the ordering of lipid molecules deposited on a silver electrode

Abstract: Dipalmitoylphosphatidylcholine lipid molecules adsorbed on a silver electrode were found to exhibit a conformational phase transition when investigated by means of surface-enhanced Raman scattering. The observed order-todisorder transition of the hydrocarbon chain is voltage dependent and exhibits hysteresis phenomena. It is suggested that the adsorption of lipid molecules occurs at the phosphocholine moiety and the kinetic process for the transition involves a voltage-induced conformational change of the head… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The bands at ca. 1432 and 1452 cm −1 are assigned to CH 2 scissoring modes and bands of 1390 cm −1 corresponds to CH 2 wagging mode (w(CH 2 )) [13,[26][27][28]. The broad bands at 1590 cm −1 are assigned to graphitic carbon originating from a photochemical reaction between CO 2 present in air or water and the silver layer [29,30].…”
Section: Sers Of Oda Langmuir Monolayermentioning
confidence: 99%
“…The bands at ca. 1432 and 1452 cm −1 are assigned to CH 2 scissoring modes and bands of 1390 cm −1 corresponds to CH 2 wagging mode (w(CH 2 )) [13,[26][27][28]. The broad bands at 1590 cm −1 are assigned to graphitic carbon originating from a photochemical reaction between CO 2 present in air or water and the silver layer [29,30].…”
Section: Sers Of Oda Langmuir Monolayermentioning
confidence: 99%
“…Studies of phospholipid films in dispersions, Langmuir layers, and Langmuir–Blodgett layers are well documented as biological membrane models 1. These assemblies have been studied by a wide range of techniques including NMR spectroscopy,2–14 X‐ray and electron diffraction,15–17 fluorescence spectroscopy,18–32 optical and spectroscopic microscopy,20, 22, 24, 33 scanning probe microscopies,34–37 and the vibrational spectroscopies FTIR,38–51 Raman,42, 52–63 and vibrational sum‐frequency generation 64–66. The vibrational spectroscopies provide much needed data about molecular structure and interactions between lipid molecules in such assemblies, particularly for the alkyl chain.…”
Section: Introductionmentioning
confidence: 99%
“…Because SERS relates to the surface phenomenon and is more complicated process than normal Raman scattering, many factors set the SERS profile. For instance, the changes of adsorbate/analyte spectral features can be caused by any of the following reasons: molecule reorientation, conformational transitions, protonation of functional group, coadsorption of ions, and so forth . In a number of recent studies, it was found that an aggregation of metal nanoparticles also can induce the changes of SERS profile .…”
Section: Introductionmentioning
confidence: 99%